A 20‐Gbps Beam‐Steered Infrared Wireless Link Enabled by a Passively Field‐Programmable Metasurface. Issue 1 (16th November 2020) - Huang, Jianou; Li, Chao; Lei, Yu; Yang, Ling; Xiang, Yuanjiang; Curto, Alberto G.; Li, Zilun; Guo, Lei; Cao, Zizheng; Hao, Yue; Koonen, Antonius Marcellus Jozef
Abstract: Beam steering is one of the main challenges in energy‐efficient and high‐speed infrared light communication. To date, active beam‐steering schemes based on a spatial light modulator (SLM) or micro‐electrical mechanical system (MEMS) mirror, as well as the passive ones based on diffractive gratings, are demonstrated for infrared light communication. Here, for the first time to the authors' knowledge, an infrared beam is steered by 35° on one side empowered by a passively field‐programmable metasurface. By combining the centralized control of wavelength and polarization, a remote passive metasurface can steer the infrared beam in a remote access point. The proposed system has the scalability to support multiple beams, flexibility to steer the beam, high optical efficiency, simple and cheap devices on remote sides, and centralized control (low maintenance cost), while it avoids disadvantages such as grating loss, a small coverage area, and a bulky size. Based on the proposed beam‐steering technology, a proof‐of‐concept experiment system with a data rate of 20 Gbps is also demonstrated. Abstract : A 20‐Gbps 2D beam‐steered infrared wireless link is demonstrated. It is enabled by a passively field‐programmable metasurface, centrally controlled by wavelength and polarization. The proposed system keeps high scalability to support multiple beams, flexibility to steer the beam, high optical efficiency, simple and cheap devices on remote sides, and centralized control to lower maintenance cost.